Character Education Management At Universitas Negeri Yogyakarta and Lajpat Rai DAV College Jagraon India (Eduscotech, 2023)
The success of an educational program can be measured based on the achievements it has achieved, both regarding its design and level of management. At Yogyakarta State University and LR DAV College Jagraon India, character education has been institutionalized, and is a priority for campus programs with government support implicitly emphasizing the importance of character education in higher education. The results of the study show that: 1) character education management at Yogyakarta State University and LR DAV College Jagraon India has so far applied management principles; 2) There are obstacles in the implementation of character education management at Yogyakarta State University and LR DAV College Jagraon India; 3) The efforts made by schools in the implementation of character education management are the formation of a team of implementing and monitoring character education; evaluating the development of character education based on the results of the teacher's assessment, conducting intensive outreach to teachers, employees, and students regarding character education programs both through curricular and extracurricular activities.